A Contemporary Multifaceted Insight into the Association Between Diabetes Mellitus and Diverticular Disease: An Update About Geriatric Syndrome - Ridwan Hashi; Rahma Thamer; Ahmed Hassan; Khalid Canna; Musaab Ahmed; Mohamed T. Hassan; Safaa Badi; Mohamed H. Ahmed (Geriatrics)
Introduction: Diverticular disease, once considered a rare geriatric gastrointestinal condition, has now become a prevalent disorder associated with increased morbidity and healthcare costs. The spectrum of complications from diverticular disease ranges from incidental findings to more serious issues such as bleeding and diverticulitis. Symptomatic diverticular disease represents a significant economic burden in the western world. Diabetes mellitus is a major global health issue. As global aging accelerates, geriatric syndromes such as diabetes mellitus (DM) and diverticular disease (DD) are becoming increasingly prevalent. Understanding their interplay is critical, particularly within the geriatric population. Both conditions are linked to lifestyle, dietary habits, and changes in gut physiology. Additionally, age-related alterations in the gut microbiome and immune system make this association more complex, contributing to morbidity and healthcare burdens in older adults. The primary aim of this review is to provide an update on the association between diabetes mellitus and diverticular disease. Methods: This narrative review explores the association between diabetes mellitus and diverticular disease. Relevant articles were identified by searching major databases. Results: Risk factors for diverticular disease include insulin resistance, diabetes mellitus, smoking, non-alcoholic fatty liver disease, lack of physical activity, a low-fibre diet, and a high-carbohydrate diet. These risk factors are also associated with the development of diabetes mellitus. Major population studies indicate that diabetes can either increase the risk of diverticular disease or have a neutral impact. A complication of diabetes mellitus includes impaired intestinal peristalsis and enteric nervous system dysfunction, which can ultimately lead to the formation of intestinal diverticula. High-calorie foods low in fibre are a staple in the diets of many type 2 diabetes mellitus patients, contributing to gut dysbiosis. A detrimental consequence of dysbiosis is a breach in the protective intestinal barrier, which promotes the development of diverticulosis. Conclusions: Diabetes mellitus may be associated with diverticular disease, and the risk factors that contribute to diabetes mellitus can also be linked to diverticular disease. Further studies are needed to explore the complex relationship between diabetes mellitus and diverticular disease.